Innovative Models for SMK and Industry Partnerships Aligned with the Merdeka Belajar Curriculum - Dimas Ahmad; Imam Mahir; C. Rudy Prihantono (PT. Anagata Sembagi Education, 2024)
The Merdeka Belajar curriculum represents a significant shift in Indonesia's educational landscape, emphasizing freedom in learning and the development of critical thinking and practical skills. Vocational High Schools (SMKs) play a crucial role in preparing students for the workforce, and effective industry partnerships are essential for achieving the curriculum’s goals. Despite their importance, there is a lack of innovative models that facilitate these partnerships effectively. This study aims to explore and propose innovative models for SMK-industry partnerships that align with the Merdeka Belajar curriculum. By identifying and evaluating these models, the study seeks to enhance the quality of vocational education and better prepare students for employment. The research employs a mixed-methods approach, combining qualitative and quantitative data collection techniques. Surveys and interviews with key stakeholders, including educators, industry partners, and policymakers, were conducted to gather insights. Additionally, case studies of successful SMK-industry partnerships were analyzed to identify best practices. The data were then synthesized to develop and evaluate innovative partnership models. Results of the study identify three innovative models for SMK-industry partnerships: Model A, which focuses on co-designed curriculum development; Model B, which emphasizes dual apprenticeship programs; and Model C, which integrates real-world projects into the learning process. Each model was evaluated based on criteria such as effectiveness, scalability, and sustainability. The findings indicate that these models significantly enhance student engagement, skill acquisition, and employability.